Pendampingan UMKM “Ali Serba Alat” dalam Penguatan Digitalisasi Usaha melalui Branding dan Pemasaran Online - Citra Dwi Marlia R; Nasihiyah Purwaning Wulan; Ayu Sukma Arsy Diana; Sudarmiatin Sudarmiatin; Ruly Wiliandri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service program aims to increase the digitalization capacity of the "Ali Serba Alat" MSME by strengthening Branding and Online marketing aspects. The main problems faced by partners include weak brand identity, limited use of digital media, and suboptimal Online platform-based marketing strategies. The activity implementation method uses a participatory approach with the stages of problem identification, program planning, training, mentoring, and evaluation. Activities carried out include creating a digital store presence in the form of a Google Map, logo and visual identity of the business, optimizing social media and marketplace accounts, compiling digital promotional content, and training in digital-based marketing strategies. The results of the activity show an increase in partners' understanding of the importance of Branding, improved skills in managing digital media, and increased business visibility on Online platforms. In addition, there was an increase in consumer interaction and sales potential after the implementation of the digital marketing strategy. This program is expected to become a model for sustainable mentoring in supporting the digital transformation of MSMEs to increase competitiveness in the digital economy era.